Enhancing Students’ Critical Writing Skills through Experiential Learning: Evidence from Secondary Education Contexts - Fatin Nadifa Tarigan; Siti Aminah Hasibuan; Epi Supriyani Siregar (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
This study examines the effectiveness of experiential learning in improving students’ critical writing skills in secondary education settings. Using a quasi-experimental design, 60 students were assigned to either an experimental group or a control group. The experimental group was taught through Kolb’s experiential learning approach, whereas the control group received conventional instruction. Data were gathered through pre-tests and post-tests evaluated using a critical writing rubric that emphasized argumentation, use of evidence, and coherence. The results demonstrated a substantial improvement in the experimental group’s critical writing performance. The mean score increased from 62.4 on the pre-test to 81.7 on the post-test, indicating a gain of 19.3 points. Meanwhile, the control group showed a more modest improvement, with scores rising from 63.1 to 70.2, resulting in a gain of 7.1 points. An independent samples t-test confirmed a statistically significant difference between the two groups (p < 0.01). These findings indicate that experiential learning can effectively enhance students’ critical writing abilities by encouraging active participation and reflective learning experiences.